Measurement of some properties of binderless particleboards made from young and old oil palm trunks - Junidah, Lamaming; Rokiah, Hashim; Othman, Sulaiman; Tomoko, Sugimoto; Masatoshi, Sato; Salim, Hiziroglu (Elsevier B.V., 2014)
The objective of this study was to evaluate variation of mechanical and physical properties of binderless particleboard panels manufactured from raw material of young and old oil palm (Elaeis guineensis) trunks. Results revealed that such experimental panels made from particles of young oil palm trunks had higher mechanical characteristics than those of made from old trunks. Addition of sugar compounds in the samples produced having particles from young trunks with and without extracted material enhanced their bending and internal bond strength values. Overall dimensional stability in the form of thickness swelling and water absorption those panels made from young trunks was adversely influenced. However adding sugars in the samples improved their thickness swelling and water absorption in both cases of with and without applying of extraction process.